Application timing affects the efficacy of Bacillus thuringiensis subsp. kurstaki against Tortrix viridana in deciduous oak forests - Roberto Mannu; Maurizio Olivieri; Luca Ruiu; Giuseppe Serra; Maria Leonarda Fadda; Andrea Lentini (Biological Control)
The green oak leaf roller moth, Tortrix viridana, is one of the main defoliators of deciduous oaks in the Mediterranean region. Although aerial applications of Btk-based insecticides represent the most effective method to control the larval populations of this pest at a large spatial scale, the optimal time window for sprayings has not yet been defined. Accordingly, experimental trials were conducted in a Quercus pubescens forest district in Sardinia (Italy) involving both large-scale aerial treatments and small-scale applications from the ground. The aim of our work was to study how different larval development stages and/or sprouting phenological phases of the host trees affect Btk efficacy. Aerial sprayings were conducted in 2003 and 2004 in two different areas of about 300 ha, selected according to altitude and exposure to simulate three different application timings against different larval instars and sprouting phenological phases. From-the-ground applications were carried out in 2021 in a Q. pubescens forest stand by applying Btk-based insecticides at different timings, and the overall Q. pubescens phenological stage and the distribution of T. viridana larval development stages were assessed accordingly. The effectiveness of Btk applications was evaluated by estimating larval mortality 7, and 14 days after aerial applications, and 7, 14 and 21 days after ground applications. Defoliation due to T. viridana was also evaluated at the end of larval development in all years. In both 2003 and 2004, the average larval mortality due to Btk exceeded 80 % two weeks after aerial applications across all application timings. Damage caused by T. viridana varied with Btk application timing, with the later applications showing a higher defoliation than other timings. In ground application experiments, larval mortality significantly increased when Btk was sprayed against a larval population primarily composed of IV instars, which were feeding on sprouts with leaves that were spread out and had not fully developed internodes, thus resulting in a significative reduction of insect damage. Our findings indicate that, in accordance with the strict synchrony between the larval development and the oak flushing, the optimal timing for Btk application against T. viridana can be defined based on the bud burst phenological phase. In particular, the prevalence of sprout with expanding leaf surface allowing insecticidal droplet interception and the simultaneous presence of susceptible larval instars (within the IV), resulted in an increased treatment efficacy.